2022
DOI: 10.1097/meg.0000000000002462
|View full text |Cite
|
Sign up to set email alerts
|

The role of noninvasive scoring systems for predicting cardiovascular disease risk in patients with nonalcoholic fatty liver disease: a systematic review and meta-analysis

Abstract: Backgrounds Cardiovascular disease (CVD) is suggested as a leading cause of death among patients with nonalcoholic fatty liver disease (NAFLD). The aim of this work was to clarify the role of noninvasive scoring systems (NSSs) in predicting CVD risk among this population. Methods The PubMed, Web of Science, and Cochrane databases were searched until 23 March 2022. Meta-analysis was performed for three most commonly used NSS separately, that is, fibrosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The three markers have been used to predict liver-related outcomes [18][19][20] and extrahepatic events, including cardiovascular diseases, in NAFLD patients. [21][22][23] Additional applications of seromarkers, such as the enhanced liver fibrosis (ELF) score 24 or FibroTest 25 may add value to the diagnosis of liver fibrosis. However, testing of the extracellular matrix is often on a research basis, and the cost-benefit may be offset and impractical in community screening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The three markers have been used to predict liver-related outcomes [18][19][20] and extrahepatic events, including cardiovascular diseases, in NAFLD patients. [21][22][23] Additional applications of seromarkers, such as the enhanced liver fibrosis (ELF) score 24 or FibroTest 25 may add value to the diagnosis of liver fibrosis. However, testing of the extracellular matrix is often on a research basis, and the cost-benefit may be offset and impractical in community screening.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the serum albumin level, which is associated with liver functional reserve, two additional metabolic factors, body mass index and fasting plasma glucose, were added to increase its predictive value. The three markers have been used to predict liver‐related outcomes 18–20 and extrahepatic events, including cardiovascular diseases, in NAFLD patients 21–23 . Additional applications of seromarkers, such as the enhanced liver fibrosis (ELF) score 24 or FibroTest 25 may add value to the diagnosis of liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Han et al demonstrated that significant fibrosis, as defined by the NFS and Fib-4, was associated with an increased risk of atherosclerotic CVD in patients with NAFLD (aOR = 2.38; p < 0.001) [ 30 ]. In a meta-analysis, Fib-4 and NFS, rather than the AST-to-platelet ratio index, might be a significant noninvasive fibrosis scoring system for estimating higher CVD events in patients with NAFLD [ 33 ]. In another study, high liver fibrosis scores, as defined by low FIB-4 and NFS COVs, were associated with an approximately two-fold increased adjusted risk of CVD events (cardiovascular death, nonfatal myocardial infarction, and ischemic stroke) in patients who underwent coronary interventions [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite growing awareness of the cardiovascular implications of MASLD, there is ongoing debate regarding the optimal strategy for assessing CVD risk in affected individuals. While traditional risk factors for CVD are well-established [10] , there is increasing recognition of the importance of incorporating liver-specific parameters into CVD risk assessment algorithms for MASLD patients [11][12][13] . These hepatological parameters may offer unique insights into the complex interplay between metabolic dysfunction, steatotic liver disease (SLD), and cardiovascular health.…”
Section: Introductionmentioning
confidence: 99%